UJI FRAKSI ETIL ASETAT DAUN Peronema canescens TERHADAP Plasmodium berghei PADA Mus musculus - Fuji Ramadenti; Agus Sundaryono; Dewi Handayani (ALOTROP, 2017)
[DETERMINATION OF ETHYL ACETATE FRACTION FROM Peronema canescens LEAF EXTRACT  AGAINST Plasmodium berghei  INFECTED  Mus musculus] This study was conducted to identify secondary metabolite compounds contained in ethanol extract and ethyl acetate fraction from Peronema canescens leaf (sungkai) and to measure the effect of ethyl acetate fraction on anti plasmodium  activity on Mus musculus infected by  Plasmodium berghei. The ethyl acetate extract was obtained by maceration of leaves with 96% ethanol solution in3 days followed by fractionation by ethyl acetate for further test. 25 of male white  M. musculus  with the weight 20-40 g and 6-8 weeks old , divided into 5 groups with 5 head / group. Groups 3, 4 and 5 are treated and groups 1 and 2 are controls. The negative control will be given food and drink only, and for positive control group will be given chloroquine with dose  0,028,  0,056, and  0,084 g / KgBW.  Development of levels of parasitemia were calculated by by observing a thin blood smear with giemsa staining under a microscope , observed until the parasitemia in the blood had reached 20-30% to be given a 3-day follow-up treatment, and then for the next 7 days after it was given treatment.. Anti-plasmodium activity test is determined by the number of parasitemia, percent growth and resistance of parasitemia in the blood. Data were analyzed by using one way anova method (? = 0,05 and 0,01). The results showed that the secondary metabolite compounds found in the ethyl acetate fraction of  P.canescens leaf, namely alkaloids, flavonoids, tannins and phenolics and at a dose of 0.056 g / KgBW  ethyl acetate fraction  can inhibit the growth of parasitemia in the blood of  M. musculus by 50 , 89% , with greater percentage of parasitemic inhibition compared with positive and negative control group.